2012
DOI: 10.1097/nxn.0b013e3182573b04
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Nurse Attitudes Before Implementation and 6 and 18 Months After Implementation of an Electronic Health Record

Abstract: The implementation of an electronic health record is a dramatic change in a healthcare organization; however, little is known about how nurse attitudes toward the electronic health record change over time. The purpose of this research project was to compare nurses' attitudes before and at 6 and 18 months after implementation of a comprehensive electronic health record. A presurvey-postsurvey design using a modified Nurses' Attitudes Toward Computerization Questionnaire was implemented with a population of nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
1
16
2
Order By: Relevance
“…It has been previously reported that nurses were uncertain, though hopeful, about EHR benefits prior to implementation. 19 Our study revealed a similar finding, as the nurses reported optimism both before and after implementation. Laramee et al 19 reported ongoing concerns after implementation of an EHR, including challenges with documentation and interdisciplinary communication.…”
Section: Discussionsupporting
confidence: 87%
“…It has been previously reported that nurses were uncertain, though hopeful, about EHR benefits prior to implementation. 19 Our study revealed a similar finding, as the nurses reported optimism both before and after implementation. Laramee et al 19 reported ongoing concerns after implementation of an EHR, including challenges with documentation and interdisciplinary communication.…”
Section: Discussionsupporting
confidence: 87%
“…The main challenges are around the documentation processes and difficulties in interdisciplinary communication67; face-to-face communication between nurses and doctors may be significantly reduced post-EPR implementation 68. It is therefore important that senior nurses are involved early to reduce these effects and encourage uptake 69…”
Section: Resultsmentioning
confidence: 99%
“…Shoham and Gonen, Brumini et al ., Simpson and Kenrick, McNeil et al . and Laramee et al . reported that nurses' computer‐related attitudes were generally positive.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Several studies in the international literature have analysed nurses' computer literacy, their attitudes towards computer use and the determinants of these attitudes. 4,5,[10][11][12][13][14][15][16][17][18][19][20] Shoham and Gonen, 5 Brumini et al, 18 Simpson and Kenrick, 20 McNeil et al 21 and Laramee et al 22 reported that nurses' computer-related attitudes were generally positive. On the other hand, Campbell and McDowell 23 reported that the nurses in their study had little to no experience with nearly half of the items in the Gassert/McDowell Computer Literacy Survey.…”
Section: Introductionmentioning
confidence: 99%